Tropospheric ozone and aerosol variability observed at high latitudes with an airborne lidar - Browell, Edward V.; Kooi, Susan A.; Grant, William B.; Fenn, Marta A.; Butler, Carolyn F. (1994)
Large-scale summertime (July-August) distributions of O3 and aerosols were observed in a broad range of atmosphere conditions over the tundra, ice, and ocean regions near Alaska in 1988 and over the lowlands and boreal forests of Canada in 1990. The tropospheric O3 budget in the high-latitude regions was found to be strongly influenced by stratospheric intrusions, and deposition at the surface was found to be the main sink for O3 in the troposphere. Enhanced levels of O3 were observed in plumes from fires in Alaska and Canada. This paper discusses the large-scale variability of O3 and aerosols observed in the high-latitude regions during these field experiments.